Age estimation from developing third molars - Wilson, Yvonne Padmini (Sage Publications Ltd, 2021)
We investigated the development of third molars among Malaysians (including variations between jaws and genders) using Demirjian's method. Dental panoramic radiographs of 1224 subjects aged 8 to 24 years were examined, and the molars were assigned Demirjian et al.'s development grades (A-H). Results indicated that 18.8 had congenitally missing or extracted third molars. Development of molars begins earlier in females (also in the mandible), but by age 9, male children's molar development speeds up with more advanced grades in their middle teens than females. Grade C indicates the subject is a juvenile, while initiation of root development (Grade E), was observed from 13 years on. Grade H can occur in a child aged 18 years who technically is still a juvenile. We compared the development and growth patterns of the third molar from both the maxilla and the mandible.